Penggunaan Flip Builder untuk Meningkatkan Kualitas Pembelajaran - Nuhamara, Yuliana Tamu Ina; Ndakularak, Iona Lisa; Bima, Stevvileny Angu; Wadu, Darius Imanuel; Taunu, Elsy Senides Hana; Nggaba, Mayun Erawati; Randjawali, Erwin; Priyastiti, Itha (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Implementing the Flip Builder training at SMA Matawai La Pau aims to introduce technological innovation to teachers to enhance the quality of education. This activity involves preparing training materials, distribution of invitations, and venue preparation. Throughout the training, teachers are guided to understand and apply the steps of using Flip Builder, including creating flip book products. The participants' enthusiasm is evident from their dedication during the product creation simulation and active engagement in the question-and-answer and discussion sessions. The training results indicate that teachers can overcome technical challenges effectively and are motivated to continue innovating in their teaching practices. The product creation simulation using Flip Builder provides practical insights, and teachers appear confident in utilizing the application to create engaging learning materials. Evaluation and feedback from participants serve as a foundation for improving the quality of future training sessions. As a follow-up, continuous support is essential, whether through mentoring sessions or monitoring the use of Flip Builder. Collaboration among teachers should be enhanced through forums or regular meetings. The development of additional materials and advanced training can further support teachers in maximizing the potential of Flip Builder. Overall, this training represents a positive step in promoting technology-based education at SMA Matawai La Pau.